Diseño e implementación de un simulador didáctico de control para una subestación eléctrica de doble barra con seccionador de transferencia acople. (2021)
This qualitative experimental project is developed based on a practical need in the undergraduate students of Electromechanical Engineering - Tunja Headquarters. Based on the identification of the configuration of the most used substation in the National Transmission System (STN), a didactic control simulator is designed and implemented to develop practical skills in the execution of operational maneuvers.